Вплив технологічних параметрів відцентрового обрушувача на ефективність вилучення ядра насіння конопель - Петраченко, Дмитро Олександрович; Petrachenko, Dmytro (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У роботі досліджено вплив ключових технологічних параметрів на ефективність механічно- го обрушування насіння промислових конопель. Установлено, що найбільший вплив на процес відділення оболонки від ядра має фракційний склад насіння: дрібна фракція насіння (<2,5 мм) забезпечує мінімальний вихід ядра (<10 %), середня фракція (2,5–3,0 мм) – до 17 %, а велика (>3,0 мм) – 20–22 %. Оптимальна частота обертання робочого органу становить 2 000 об/хв, оскільки перевищення цього значення спричиняє надмірне подрібнення ядра. Вологість насіння має незначний вплив на ефективність процесу обрушування, а її оптимальне значення визначено на рівні 16,3 %. Виявлено, що досліджувані фактори на процес обрушування насіння промислових конопель впливають незалежно, без суттєвої взаємодії між собою. Отримані результати можуть бути використані для вдосконалення конструкції обрушувальних пристроїв та розробки оптимальних технологічних режимів їх роботи. /// EN: The study examines the influence of key factors, such as seed fraction size, rotor speed, and raw material moisture content, on the efficiency of kernel separation from the hull. The research was conducted using an experimental centrifugal sheller, which allowed for the determination of optimal operating parameters to achieve maximum kernel yield. It was established that the seed fraction size is the most critical factor in the shelling process. The small fraction (<2.5 mm) provides a minimal kernel yield (<10 %). The medium fraction (2.5–3.0 mm) demonstrates an increase in yield up to 17 %, while the large fraction (>3.0 mm) ensures the highest kernel extraction rate of 20–22 %. The optimal rotor speed was determined to be 2000 rpm. Reducing this parameter to 1500 rpm decreases the efficiency of hull destruction, while increasing it to 2500 rpm leads to excessive kernel fragmentation, resulting in higher waste production and reduced final product quality. An analysis of seed moisture content showed that this parameter has a secondary effect, as moisture levels within the range of 8.8 %–21.6 % have only a slight impact on kernel yield. The optimal moisture content was determined to be 16.3 %, at which the best balance between shelling efficiency and minimizing the amount of unshelled product is achieved. It was found that the studied technological parameters affect the shelling process independently, without significant interaction between them. This allows for the determination of optimal operating modes of the equipment by varying each factor separately. The obtained results can be used to improve the design of shelling devices and to develop optimal technological regimes for mechanical shelling of industrial hemp seeds, aiming to minimize processing losses and maximize the yield of high-quality kernels.
Impact of technological parameters of a centrifugal sheller on the efficiency of kernel extraction from hemp seeds
Keywords: коноплі; фракція насіння; параметри обрушування; вихід ядра; відцентровий обрушувач; hemp; seed fraction; shelling parameters; kernel yield; centrifugal sheller